EphrinB2 regulates VEGFR2 during dendritogenesis and hippocampal circuitry development - Harde, Eva; Nicholson, LaShae; Furones Cuadrado, Beatriz; Bissen, Diane; Wigge, Sylvia; Urban, Severino; Segarra, Marta; Ruiz de Almodóvar, Carmen; Acker-Palmer, Amparo (eLife, 2019)
Vascular endothelial growth factor (VEGF) is an angiogenic factor that play important roles in the nervous system, although it is still unclear which receptors transduce those signals in neurons. Here, we show that in the developing hippocampus VEGFR2 (also known as KDR or FLK1) is expressed specifically in the CA3 region and it is required for dendritic arborization and spine morphogenesis in hippocampal neurons. Mice lacking VEGFR2 in neurons (Nes-cre Kdrlox/-) show decreased dendritic arbors and spines as well as a reduction in long-term potentiation (LTP) at the associational-commissural - CA3 synapses. Mechanistically, VEGFR2 internalization is required for VEGF-induced spine maturation. In analogy to endothelial cells, ephrinB2 controls VEGFR2 internalization in neurons. VEGFR2-ephrinB2 compound mice (Nes-cre Kdrlox/+ Efnb2lox/+) show reduced dendritic branching, reduced spine head size and impaired LTP. Our results demonstrate the functional crosstalk of VEGFR2 and ephrinB2 in vivo to control dendritic arborization, spine morphogenesis and hippocampal circuitry development.
Gesehen am 17.04.2020